Optimizing Tourist Destination Selection in Aceh Besar through MOORA-Based Decision Support System - Ahmad, Nazaruddin; Salwa, Tin; Husaini, Nazmi Al; Haikal, Nadia; Faiqa, Athiya; Phonna, Zahara; Rahmani, Syifaur (Universitas Putra Indonesia YPTK Padang, 2025)
This study is motivated by the abundant tourism potential in Aceh Besar that has not yet been supported by a recommendation system capable of providing measurable information regarding travel cost, distance, travel time, facilities, and cleanliness, which often makes it difficult for tourist to determine the optimal destination. The objective of this research is to provide the best tourism destination recommendations by applying the Multi-Objective Optimization on the Basis of Ratio Analysis (MOORA) method within a web-based Decision Support System. The calculation process was carried out through the stages of normalization, weighting, and ranking based on the five predetermined criteria. The results indicate that the three top-ranked tourism destinations recommended are Eky Momong Resort (A6) as the first rank with a score Yi=0.0676, Air Terjun Elnaja (A9) as the second rank with a score Yi=0.0619, and Pucok Krueng (A10) as the third rank with a score of Yi=0.0350. With the development of this web-based system, tourist are able to obtain recommendations that are more objective, efficient, and aligned with relevan criteria.